Mahkamah Konstitusi Di Persimpangan: Menelusuri Upaya Pelemahan Dan Dampaknya Bagi Hukum Dan Demokrasi - Salsabil, Hilda Halnum (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: This article discusses the position of the Constitutional Court (MK) in Indonesia in the context of the attempts to weaken it and its impact on law and democracy.Purposes of the Research: This research identifies several factors that contribute to the Constitutional Court's challenges, such as political interference, corruption, and legislation that harms the institution's independenceMethods of the Research: Using literature methods, this research analyzes various secondary sources, including books, academic articles, and official reports relating to constitutional and judicial issuesResults of the Research: Weakening of the Constitutional Court (MK) can be divided into two categories: external and internal. External factors include the lack of strengthening authority in the Constitutional Court Law, political efforts in appointing judges, and the removal of judges by the DPR without legal basis. Meanwhile, internal factors come from ethical violations of judges affiliated with politics and inconsistencies in decisions. Strengthening the Constitutional Court institution is needed through a transparent judge selection process and supervision from the Judicial Commission, concluding that efforts to strengthen the Constitutional Court are very important in maintaining justice and democracy in Indonesia. Recommendations are proposed to increase the independence and accountability of the Constitutional Court, including the need for structural reform and strengthening supervisory mechanisms. Thus, this research contributes to understanding the importance of the role of the Constitutional Court in a healthy legal system and democracy.